Chemsex practices and pre-exposure prophylaxis (PrEP) trajectories among individuals consulting for PrEP at a large sexual health clinic in Montréal, Canada (2013-2020). (1st September 2021) - Flores Anato, Jorge Luis; Panagiotoglou, Dimitra; Greenwald, Zoë R.; Trottier, Claire; Vaziri, Maliheh; Thomas, Réjean; Maheu-Giroux, Mathieu
Highlights: One in four gbMSM consulting for PrEP in Montréal reported chemsex in the past year. Ecstasy, GHB and cocaine are the most common chemsex substances reported. Chemsex is not a barrier to PrEP initiation or persistence among gbMSM. Abstract: Introduction: Chemsex among gay, bisexual and other men who have sex with men (gbMSM) has raised public health concerns because of its association with sexual behaviours that can increase transmission of sexually transmitted infections, including HIV. Pre-exposure prophylaxis (PrEP) is highly effective at blocking HIV acquisition, addressing important prevention needs among individuals practicing chemsex. This study aims to improve our understanding of chemsex practices and PrEP trajectories of gbMSM and transgender women consulting for PrEP. Methods: We used data from the PrEP cohort of Clinique médicale l'Actuel, a major sexual health clinic in Montréal. We describe the sociodemographic profile of clients consulting for PrEP, characterize chemsex and polysubstance use trends over time, and evaluate PrEP trajectories using Kaplan-Meier curves. Results: Among 2923 clients who consulted for PrEP between 2013–2020 (2910 cisgender gbMSM, 6 transgender gbMSM, 7 transgender women), 24 % reported chemsex in the past year and 13 % reported polysubstance use. The most common chemsex substances were ecstasy (14 %), GHB (13 %), and cocaine (12 %). The proportion of clients reporting chemsex and polysubstance use decreased over time. In both the chemsex and no-chemsex group, 73 % of clients initiated PrEP. The median time to discontinuation was similar between the chemsex (6.5 months; 95 %CI: 5.3–7.2) and no-chemsex group (6.9 months; 95 %CI: 6.3–7.5). Conclusion: Chemsex is not a barrier to PrEP initiation or persistence. However, these results suggest a high prevalence of chemsex among gbMSM consulting for PrEP, highlighting the need for services addressing the intersection of sexual health and substance use for this population.